The Effects of Instagram Media with Inquiry on Critical Thinking Skills in The Topic Reaction Rates - Rose, Roro Roudotul Rohmatin; Yamtinah, Sri; Ulfa, Maria; Widarti, Hayuni; Shidiq, Ari Syahidul (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
In the 21st century, social media has emerged as a potential educational tool to enhance learning outcomes and critical thinking skills. To explore this, a study assessed whether Instagram, employed as a learning media for inquiry-based chemistry learning, influences students' critical thinking abilities. The research adopted a quasi-experimental design, utilizing a pretest-posttest nonequivalent control group approach in eleventh-grade science classes across Senior High Schools in Surakarta. The research focused on reaction rates due to its abstract nature and visualization challenges. Random sampling was employed to select 72 students aged 16 to 18, divided into experimental and control groups. The research instrument encompassed 24 questions in pretest and posttest formats, comprising multiple-choice and essay-type questions. N-Gain analysis revealed a noteworthy increase in learning outcomes within the experimental group, registering a value of 0.79, surpassing the control group's value of 0.69. This underscores Instagram's efficacy as a learning tool, outperforming conventional teaching methods. Regarding critical thinking skills, the experimental group displayed the highest competence in indicators such as explanation, self-regulation, evaluation, analysis, and conclusion. The study establishes that when integrated into chemistry education with an inquiry-based model, Instagram positively impacts students' critical thinking skills, specifically about reaction rates. This research contributes novel insights into the application of Instagram for chemistry education and pioneers the examination of critical thinking skills within this context, enriching the domain of chemistry learning.